FOREIGN EXCHANGE MARKET OF UZBEKISTAN AND ITS INTEGRATION INTO THE INTERNATIONAL CURRENCY MARKET - Berdiqulova Sevinch Tohir qizi (Journals Park Publishing, 2022)
The article contains statistical data and relevant conclusions regarding the effective organization of the currency system of our country and strengthening its integration into the international currency market in the development of international financial relations
Keywords: Currency policy; Currency exchanges; Foreign exchange funds